Field notes from a catastrophe man, nature, and climate change - Kolbert, Elizabeth (Bloomsbury Publishing, 2006)
New Yorker writer Kolbert tackles the controversial subject of global warming. Americans have been warned since the late 1970s that the buildup of carbon dioxide in our atmosphere threatens to melt the polar ice sheets and irreversibly change our climate. With little done since then to alter this dangerous course, now is the moment to salvage our future. By the end of the century, the world will likely be hotter than it's been in the last two million years, and the sweeping consequences of this change will determine the future of life on earth for generations to come. Kolbert approaches this monumental problem from every angle. She travels to the Arctic, interviews researchers and environmentalists, explains the science and the studies, draws frightening parallels to lost ancient civilizations, unpacks the politics, and presents the personal tales of those who are being affected most--the people who make their homes near the poles and are watching their worlds disappear.--From publisher description.